ANALYSIS OF FAMILY NURSING CARE WITH FOOD DIARY INTERVENTIONS ON WEIGHT LOSS IN ADOLESCENTS IN RW 06 GROGOL VILLAGE LIMO DEPOK - Anggraini, Nourmayansa Vidya; Millenia, Ni Made Anggun (Indonesian Journal of Community Health Nursing, 2024)
Introduction: Obesity is the accumulation of excessive fat that can lead to health risks. In adolescence, obesity is at high risk and the incidence of obesity in adolescents is an indicator of a health problem and an increased risk of non-communicable diseases that occur in society. The purpose of this paper is to analyze nursing care with food diary interventions for weight loss in adolescents, where interventions are carried out by adolescents for 30 days by recording the types of food, drinks, and snacks consumed every day and monitoring weight every week. Method: . The implementation method of the intervention in the form of using a food diary for adolescents was carried out first by distributing media in the form of a diary to adolescents, then introducing the media and explaining the contents and also how to use the food diary. Results: The results showed a significant effect on weight loss in obese adolescents by providing interventions in the form of a food diary, where there was a decrease in body weight in managed and resume patients by 1.4 kg and 1.1 kg. Conclusion: Parenting in accordance with the development of adolescence must also be considered for parents in an effort to overcome the risk of obesity.